AN ANALYSIS OF THE MAIN CHARACTER’S PSYCHOLOGICAL CONFLICT IN THE NOVEL “9 SUMMERS 10 AUTUMNS: FROM THE CITY OF APPLES TO THE BIG APPLE” BY IWAN SETYAWAN - Lukman Nurwahit; Agita Violy; Rosyiadiastuti (PT. Media Akademik Publisher, 2025)
The purpose of this study is to identify and analyze conflict comprehensively in a novel. Object of this research is the novel “9 Summers 10 Autumns: From The City of Apples to The Big Apple” by Iwan Setiawan tells the story of a boy from little village who pursues his dreams in United State of America. This study discusses the psychological conflict experienced by main character, especially the conflict that happens when he has been solving the problem to reach every target what he wants. The study uses a qualitative method to determine how to analyze and collect research data, which is used to determine psychological experience. The result of this study found that as a condition when someone has been born is not a reason to create a big dream, sometimes this condition also gives trouble in relationship with friend of the same age and always haunted by feelings of guilt so punishing himself and experience the inner conflict. The data collection which we obtained from the observation, documentation, and combined. As well as the technique of analysing data which used is qualitative data analyzing, it is Reading or studying the data, Learn the keyword and write model was found. The wisdom of this study was a parents should support every dream from their children and did not give some tight limitation that made kids felt hards to achieve their dreams.